BS4 Iron deficiency in pulmonary arterial smooth muscle cells induces pulmonary arterial hypertension through endothelin-1. (May 2019) - Lakhal-Littleton, Samira; Crosby, Alexi; Mohammad, Goran; Frise, Matthew; Carr, Carolyn; Loick, Paul; Robbins, Peter
Abstract : Introduction: Iron deficiency augments hypoxic pulmonary arterial pressure in healthy individuals and exacerbates pulmonary arterial hypertension (PAH) in patients, even in the absence of anaemia. In supplementation has been shown to be beneficial in both settings. The mechanisms underlying the detrimental effects of iron deficiency and the beneficial effects of iron supplementation are not known, owing to a lack of understanding of how specific cells of the pulmonary vasculature respond to changes in iron levels. The iron export protein ferroportin (FPN) and its antagonist peptide hepcidin control systemic iron levels by regulating its release from the gut, spleen and liver, the sites of iron absorption, recycling and storage, respectively. We found FPN to be present in pulmonary arterial smooth muscle cells (PASMCs) and to be regulated by hepcidin. Therefore, we set out to interrogate the physiological function of the hepcidin/FPN axis in PASMCs. Methods: We generated a murine model with a smooth muscle-specific knock-in of fpn C326Y, which encodes a FPN with intact iron export function but impaired hepcidin binding. We then studied pulmonary hemodynamics and cardiac function over time. Results: While retaining normal systemic iron and haemoglobin levels, this model developed PAH and right heart failure as a consequence of intracellular iron deficiency and increased expression of the vasoconstrictor endothelin-1 (ET-1) specifically within PASMCs. PAH was prevented and reversed by intravenous iron treatment and by the ET receptor antagonist BQ-123. The regulation of ET-1 by iron was further demonstrated in healthy humans exposed to hypoxia and in PASMCs from PAH patients. Conclusion: This study presents the first evidence that intracellular iron deficiency localised specifically within PASMCs is sufficient to impair pulmonary vascular function, even in the absence of anaemia (fig 1). It offers a mechanistic underpinning for the known effects of iron availability on the pulmonary vasculature in the human setting. Conflict of interest: None